Exploring the development of metacognitive strategies in learning technologies among pre-service teacher trainees through an e-space community framework - Nordin, Mohd Shukri (2016)
The purpose of this study was to explore the extent of e-space community framework in developing metacognitive strategies of pre-service teacher trainees towards ICT competency in contemporary learning technologies. The e-space community framework used in this study created a virtual community of practice (VCoP) that has the possibilities of developing the trainees’ metacognitive strategies in learning technologies. The framework looks at extending Vygotsky’s concept of Zone of Proximal Development (ZPD) upon the VCoP. Evidence has shown that ZPD has the potential of helping a learner learn better by seeking guidance from surrounding peers. It is argued that the combination of ZPD and VCoP has the advantages of making teaching and learning more engaging and effective. The study proposed the use of an e-space community as the mediator to develop metacognitive strategies in learning technologies. The concept of e-space community is congruent with Wenger’s concept of Communities of Practice (CoPs), where people of the same interest do and learn better via regular interaction. It is also parallel with the earlier mentioned concept of ZPD as discussed by Vygotsky. The research used an explanatory mixed-method approach on 38 pre-service teacher trainees, where a pre-test, a mid-test and a post-test with a treatment intervention were supported by interviews. The quantitative findings of this study revealed that e-space community in this study gave very little impact on the development of the pre-service teacher trainees’ metacognitive strategies towards ICT competency in contemporary learning technologies. This was supported by the qualitative findings that concur with the fact that the participants did not prefer the official e-space platform chosen for this study and were more drawn to more convenient external platforms. The study has implications on how any official e-space platform of an institution should be designed and deployed in order to create more appeal and attract the targeted CoP to use and gain benefits from the intended objectives towards ICT competency.